2016
DOI: 10.1371/journal.pone.0153381
|View full text |Cite
|
Sign up to set email alerts
|

Kin-Aggregations Explain Chaotic Genetic Patchiness, a Commonly Observed Genetic Pattern, in a Marine Fish

Abstract: The phenomenon of chaotic genetic patchiness is a pattern commonly seen in marine organisms, particularly those with demersal adults and pelagic larvae. This pattern is usually associated with sweepstakes recruitment and variable reproductive success. Here we investigate the biological underpinnings of this pattern in a species of marine goby Coryphopterus personatus. We find that populations of this species show tell-tale signs of chaotic genetic patchiness including: small, but significant, differences in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 32 publications
4
61
1
Order By: Relevance
“…We found groups of no more than two siblings within our sampling area, in contrast to studies that identified aggregations of full siblings in coral reef systems (e.g., Selwyn et al, ; Veliz, Duchesne, Bourget, & Bernatchez, ). This suggests that physical dynamics driving aggregation might be weaker along the open coastline of California, or that our statistical power to accurately identify them is higher than that used in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…We found groups of no more than two siblings within our sampling area, in contrast to studies that identified aggregations of full siblings in coral reef systems (e.g., Selwyn et al, ; Veliz, Duchesne, Bourget, & Bernatchez, ). This suggests that physical dynamics driving aggregation might be weaker along the open coastline of California, or that our statistical power to accurately identify them is higher than that used in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…However, these approaches seldom consider the effect of fine-scale processes that are influenced by stochastic and patchy dispersal, such as high spatial coherence in the genetic structure of recruits. Such genetic patchiness can translate into cascading effects on local genetic diversity and population regulation (37,38). By demonstrating that larval aggregation can shape dispersal processes to a greater degree than previously thought, our results highlight the need to better understand the fine-scale physical and biological processes occurring in the pelagic ocean that affect the growth, survival, and dispersal of larvae.…”
Section: See Retraction Published December 18 2017mentioning
confidence: 58%
“…; Selwyn et al. ). Simulation studies have suggested that chaotic genetic patchiness is driven by (1) genetic drift created by small local effective population sizes and (2) collective dispersal at the larval phase (Broquet et al.…”
Section: Discussionmentioning
confidence: 98%
“…), which would also be expected to reinforce a pattern of genetic patchiness (Selwyn et al. ). Finally, it should be noted that the unique reproductive strategy of snook species may also play a role in the population genetic patterns observed here.…”
Section: Discussionmentioning
confidence: 99%